Praktik Investasi Emas Digital di Aplikasi Dana Dalam Perspektif Hukum Islam: Studi Kasus di Universitas Islam Batang Hari - Wahyunita Wahyunita; Mashudi Hariyanto; Musaddad Al Basry (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research was motivated by public hesitation to invest in digital gold through the Dana app, which refers to Fatwa No. 77/DSN-MUI/V/2010 concerning non-cash gold buying and selling. This fatwa serves as a guideline for Muslims investing in gold. Furthermore, the author has not found any licensing from the Sharia Supervisory Board (DPS) for the Dana app. Furthermore, several students at Batang Hari Islamic University (UNI) have the Dana app and use it to invest in gold. They were seen buying gold on a certain day and reselling it the next day. The added value from the sale was a profit for the students, but there was also a loss for students who exchanged their gold purchases when the price of gold fell. Furthermore, this research is designed in the form of field research (Empirical Jurisprudence), which is a type of sociological legal research and can be described as field research, which examines applicable legal provisions and what has occurred in community life. Using observation, interview, and documentation techniques, data analysis and triangulation are then carried out. The conclusion that can be drawn from the previous description is that the Digital Gold Investment Practice on the Dana Application at Batang Hari Islamic University in its mechanism on the Gold Fund feature is carried out non-cash where the certainty of the object, namely gold, is only in the form of savings balances in the form of rupiah and digital gold weight with no physical gold ownership if the gold savings have not reached 1 gram. In gold investment transactions on the Dana application, the results show that smaller profits are obtained by buyers due to certain problems related to the buyers themselves. The Digital Gold Investment Practice on the Dana application in the Islamic Law Perspective at Batang Hari Islamic University, by juxtaposing several related fatwas, in practice in Islamic law, the investment practice in the Gold Fund feature is considered to contain gharar related to gold objects that have no physical clarity.